2011
DOI: 10.1039/c1mt00044f
|View full text |Cite
|
Sign up to set email alerts
|

Silver and gold nanoparticles in plants: sites for the reduction to metal

Abstract: Induced formation of metal nanoparticles in living plants is poorly understood. The sites for the reduction of Ag(+) and Au(3+) to Ag(0) and Au(0) metal nanoparticles in vivo in plants were investigated in order to better understand the mechanism of the reduction processes. Brassica juncea was grown hydroponically, followed by growth in solutions of AgNO(3), [Ag(NH(3))(2)]NO(3) or HAuCl(4). Harvested plants were sectioned and studied by transmission electron microscopy. Total metal content was analysed by atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 19 publications
5
72
0
Order By: Relevance
“…On the contrary, little has been understood about this process in living plants. Beattie and Haverkamp (2011) recently investigated the location of Au and AgNPs formation within the tissues of Brassica juncea with the aim of clarifying the mechanisms of NPs formation. A couple of experimental observations were recorded.…”
Section: Reducing Agentsmentioning
confidence: 99%
“…On the contrary, little has been understood about this process in living plants. Beattie and Haverkamp (2011) recently investigated the location of Au and AgNPs formation within the tissues of Brassica juncea with the aim of clarifying the mechanisms of NPs formation. A couple of experimental observations were recorded.…”
Section: Reducing Agentsmentioning
confidence: 99%
“…When Shama et al 23 bioreduced Au 3+ to Au 0 nanoparticles in plants, they discovered an interesting phenomena that many GNPs surrounded organelles. Additionally, Beattie and Haverkamp 24 demonstrated that the site of the most abundant reduction of Au 3+ metal salts to Au 0 nanoparticles in plants were chloroplasts. This prompted the authors of the present paper to investigate the possibility of biosynthesizing GNPs using chloroplasts as biological templates.…”
Section: Introductionmentioning
confidence: 99%
“…When research had been conducted on bioreduced Au 3+ to Au 0 nanoparticles in plants by Sharma et al [80], they discovered that many gold nanoparticles surrounded organelles. Moreover, Beattie and Haverkamp [81] demonstrated that chloroplasts were the site of the most abundant reduction of Au 3+ salts to Au 0 nanoparticles in plants. This prompted the authors to investigate the possibility of biosynthesized gold nanoparticles using chloroplasts as biological templates and the chloroplasts acted in dual roles, ie as reducing agents and stabilizers in the course of the formation of gold nanoparticles [82].…”
Section: Application Of Nanoparticlesmentioning
confidence: 99%